The Political Economy of Land Finance in China. (June 2016) - Wang, Wen; Ye, Fangzhi
Abstract : The heavy reliance of Chinese local governments on land‐leasing revenues in recent decades has attracted widespread criticism due to its potential risks and problems. This research, using a panel dataset of 280 prefecture‐level cities in China from 1999 to 2009, explores what factors affect Chinese city governments' dependence on land finance. The findings provide strong support for hypotheses concerning the effects of both fiscal incentives and political incentives on local fiscal behavior. Both fiscal factors—such as local reliance on fiscal transfers and fiscal decentralization—and political factors—including local top leaders' tenure and their distance to mandatory retirement—have exerted significant impacts on city governments' reliance on land finance. These findings point to the significance of intergovernmental fiscal arrangements and political institutions in affecting local government fiscal behavior in developing countries.